Evaluation of the peak torque, total work, average power of flexor-estensor and prono-supinator muscles of the elbow in baseball players - Costantini, C.; Vaienti, E.; Pogliacomi, F. (Acta Biomedica Atenei Parmensis, 2003)
The Authors, after a short analysis on biomechanics of the elbow during throwing in baseball, show the movements of the elbow during the different phases of the throw and the stabilizing action of the ulnar collateral ligament, flexor-pronator muscles of the wirst, anconeus and brachial triceps muscles. Aim of this study is the evaluation of the peak torque, total work and average power of the flexor-extensor and pronator-supinator muscles of the elbows in professional baseball players. Isokinetic test data show that a mayor peak torque in flexo-extension at power and resistence test in the pitchers compared to the strikers. Whereas the strikers show a higher peak torque in pronation at the resistence test. This may happen because during a baseball match the ball is hit many times by the bat and the pronator muscle of the wrist are notably stimulated and rinforced.